Upaya Meningkatkan Minta Baca Siswa Sekolah Menengah Pertama Negeri 1 Pagaden Barat - Erna Nurlela; Deni Mudian (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This study aims to find alternatives to increase students' interest in reading, especially among SMPN 1 Pagaden Barat. Interest in reading is a big influence for students. Efforts to increase students' reading interest at SMPN 1 Pagaden Barat are a shared responsibility, between the students themselves, teachers and parents. However, the low reading interest of students at SMPN 1 Pagaden Barat is one of the obstacles, the lack of desire and willingness from the students themselves, the teacher also does not require students to read books when learning is being taught to students. In an effort to increase students' interest in reading at SMPN 1 Pagaden Barat, it is best if students are given support so that interest in reading emerges from students and is introduced to reading material so that these students are accustomed to reading, therefore the habit of reading in junior high school students will foster a high interest in reading. until students grow up. This research was conducted by formulating a research problem looking for references from relevant and similar journals to analyze the data, journals were collected by searching the internet through Google Chendikia and/or Google Scholar. The data obtained were analyzed and compared with this research method using a descriptive research type with a quantitative approach. From the results of the analysis it can increase students' interest in reading at SMPN 1 Pagaden Barat.